Gamification in Marketing: Leveraging Interactive Experiences for Higher Consumer Engagement - Andre Ilyas; Ahmad Vajri Rahman; Bella Hartati (International Journal of Economics and Management Research, 2025)
This study explores the role of gamification in enhancing consumer engagement within digital marketing environments by examining the mediating influence of interactive experience. Although gamified marketing systems are increasingly adopted across various industries, their effectiveness often varies due to insufficient understanding of how game elements lead to meaningful user engagement. This research addresses that gap by focusing on how interactive features such as personalization, user control, and sensory feedback transform gamification mechanics into immersive consumer experiences. Employing a qualitative methodology, the study gathered data through in depth interviews with digital marketing professionals and UX/UI designers, complemented by a systematic literature review. Thematic analysis revealed that interactive experience plays a critical role in translating game elements into cognitive, emotional, and behavioral engagement. The findings indicate that successful gamification strategies must be designed with a strong focus on the user experience, aligning game mechanics with the specific motivations and preferences of the target audience. By integrating perspectives from Self Determination Theory and Experiential Marketing Theory, the study offers a conceptual foundation for designing more effective digital engagement strategies. These insights are valuable for marketers aiming to create compelling, user centered digital experiences that foster long term consumer loyalty.